2014
DOI: 10.17341/gummfd.24326
|View full text |Cite
|
Sign up to set email alerts
|

Çi̇nko Borat Katkili Poli̇propi̇len’i̇n Reoloji̇k Özelli̇kleri̇ni̇n Beli̇rlenmesi̇

Abstract: ÖZETGerçekleştirilen bu çalışmada, toz haldeki polipropilen (PP) malzemeye ağırlıkça % 5; % 7,5; % 11,25; % 16,875 ve % 25,3125 oranlarında çinko borat ilave edilerek takviyelendirilmiş polipropilen granülleri üretilmiştir. Çinko borat katkılı polipropilenin granül üretimi esnasında karışıma, oksitlenmeyi önlemek amacıyla % 0,2 oranında antioksidan olarak maleik anhidrit katılmıştır. Kompozit granül üretildikten sonra ergiyik akış indeksi (EAİ) cihazı kullanılarak takviyelendirilmiş poliproplen'in reolojik öze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…, as colemanite content is increased, shear rate is decreased, but as pressure is increased, shear rate values increase in parallel. These results, which indicate the effects of pressure on deformation rates, are in line with the results of the studies found in literature …”
Section: Experimental Findings and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…, as colemanite content is increased, shear rate is decreased, but as pressure is increased, shear rate values increase in parallel. These results, which indicate the effects of pressure on deformation rates, are in line with the results of the studies found in literature …”
Section: Experimental Findings and Discussionsupporting
confidence: 92%
“…Accordingly, it was determined that the viscosity of colemanite‐filled PP material exhibited an overall increasing trend in response to increasing concentrations of colemanite (despite a small decrease at the 11.25 wt% concentration mix rate), and that viscosity decreased in response to increasing temperature and pressure. The results of this experimental study, in line with existing literature, exhibited increasing viscosity values up to a colemanite concentration mix of approximately 11.25 wt%. It is determined that as increased viscosity will complicate the injection molding process, remaining parameters for the injection process should be increased as well.…”
Section: Experimental Findings and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In experiments conducted with melt flow index test device, viscosity values were obtained from shear stress and corrected shear rate via Rabinowitsch equation. According to the results of the corrected shear rate and shear stress; corrected viscosity values Equation 5 were obtained from corrected shear rate section of corrected shear stress [25,26].…”
Section: Viscositymentioning
confidence: 99%